(untitled) (Community Based Medical Journal, 2025)
A cross-sectional study was conducted in the Department of Medicine, Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between July and December of 2022, to compare thyroid function, lipid profile and vitamin D levels between perimenopausal and postmenopausal women. Among 257 participants aged between 45 and 65, the control group included 100 perimenopausal women, while the study group included 157 postmenopausal women with duration not more than 5 years of menopause. Serum TSH, T4, and T3 levels (as thyroid function tests), lipid profile and vitamin D3 levels were estimated by using chemiluminescent microparticle immunoassay method and following standard laboratory procedures in an autoanalyzer. The mean age of women in the perimenopausal group was 48.6±2.7 years, while in the postmenopausal group was 56.4±3.4 years (p<0.001). There were no differences in serum TSH (2.02±0.927 μIU/ml vs. 3.30±3.632 μIU/ml), T4 (104.88±22.02 nmol/L vs. 96.98±34.14 nmol/L) and T3 (1.02±0.141 ng/ml vs. 0.92±0.144 ng/ml) levels between two groups (p>0.05). Comparing lipid profile, total cholesterol levels were 205.05±36.69 mg/dl and 223.96±36.86 mg/dl (p<0.001), HDL 65.11±16.42 mg/dl and 65.90±13.60 mg/dl (p>0.05), LDL 118.17±28.64 mg/dl and 136.59±33.56 mg/dl (p<0.001), and triglycerides levels were found 108.86±54.69 mg/dl and 107.28±53.57 mg/dl (p>0.05) respectively. No difference was also observed in vitamin D3 levels between the groups (17.09±9.37 vs. 17.31±8.79) (p>0.05). However, hyperthyroid and hypothyroid status were found in 12% vs. 14.01% and 4% vs. 4.46% respectively between two groups. In lipid profile, increased levels of cholesterol, LDL and triglycerides were observed in 64% vs. 84.08%, 54% vs. 75.16% and 17% vs. 14.65, while decreased HDL levels were found in 9% vs. 10.83% respectively between two groups. Besides, mild, moderate and severe vitamin D deficiencies were found in 22% vs. 20.38%, 42% vs. 49.05% and 26% vs. 20.38% respectively between two groups. CBMJ 2025 July: vol. 14 no. 02 P:109-114